An equivalent-circuit topology for lossy non-symmetric reciprocal two-ports - Hernández-Escobar, Alberto; Abdo-Sánchez, María Elena; Mateos-Ruiz, Pablo; Esteban, Jaime; Martín-Guerrero, Teresa María; Camacho-Peñalosa, Carlos (IEEE Journal of Microwaves, 2021)
An equivalent-circuit topology for two-port lossy non-symmetric reciprocal networks is proposed. The circuit topology is based on the eigenstate decomposition. The proposed circuit consists of two immittances and two transformers with a single complex turns ratio, all obtained from the eigenvalues and eigenvectors of the admittance or impedance matrix of the network in a straightforward way. The interconnection of the circuit elements is simple and compact, and the real parts of its immittances are always positive. To verify its behavior, the equivalent circuit of two different leaky-wave antenna unit cells is extracted: a series-fed coupled patch radiating element, and the complementary strip-slot. Simulated and measured data are provided for the study cases, highlighting the satisfactory behavior of the equivalent circuit over a very broad bandwidth. A simple asymmetry model is also proposed that can be used advantageously in the analysis and design of non-symmetric two-ports, like unit cells of leaky-wave antennas.
Keywords: Circuitos electrónicos; Asymmetry; Eigenstates; Equivalent circuits; Lattice network; Leaky-wave antenna